"When a man drinks alcohol it's cool but when a woman drinks she is a hoe": A qualitative exploration of alcohol, gender, stigma, and sexual assault in Moshi, Tanzania. - Alena Pauley; Madeline Metcalf; Mia Buono; Sharla Rent; Mariana Mikindo; Yvonne Sawe; Joseph Kilasara; Judith Boshe; Catherine A Staton; Blandina T Mmbaga (Public Library of Science (PLoS), 2024)
Alcohol's ever-increasing global use poses a distinct threat to human well-being, with intake and associated burdens rising especially quickly in low- and middle-income countries like Tanzania. Prior research has shown alcohol use and related consequences differ by gender in Moshi, Tanzania, with important implications for both clinical care and future alcohol-reduction interventions. This study builds upon this knowledge by providing a deeper understanding of how gender differences affect alcohol-related stigma and sexual assault among Emergency Department (ED) and Reproductive Health Center (RHC) patients at Kilimanjaro Christian Medical Center (KCMC) in Moshi. In-depth interviews were conducted among ED and RHC KCMC patients (n = 19) selected for participation via purposive sampling. A mix of inductive and deductive coding schemes was used to identify themes and subthemes. All data were analyzed through a grounded theory approach. Gender roles that linked men with financial responsibilities and women with child caretaking led to different expectations on alcohol intake, with alcohol use encouraged for men but vilified for women. Women who drank, for example, were deemed poor mothers and undesirable spouses. Patients likewise emphasized that both alcohol-related stigma and sexual violence disproportionately impacted women, the latter fueled through alcohol use, with serious and lasting acts of discrimination and isolation from community members seen among women alcohol users but not for men. Women alcohol users in Moshi are subject to severe social consequences, facing disproportionate stigma and sexual violence as compared to men. Alcohol-related treatment for women should be mindful of the disproportionate burdens present in this context while treatment for men should be cognizant of the social pressures to drink. Strategies to address and/or mitigate these factors should be incorporated in subsequent care and interventions.